Nursing actions that promove the security of the patient in the hospitalar scope (Research, Society and Development, 2021)
The objective of the study was to identify which strategies are implemented by nurses in the hospital area to ensure patient safety. It is an integrative literature review that sought to analyze the work of nursing in promoting patient safety in the hospital environment. For the study, articles published in the years 2015 to 2020 were used, collected in the LILACS, SCIELO and BDENF databases. After searching the proposed databases and meeting the descriptors and criteria pre-established by the authors, 25 articles were selected. The actions with the highest frequency were: permanent education (17.2%), communication (14.7%), team planning (12.2%), use of protocols for assistance (9.8%). The findings showed multiple actions performed by the nursing professional that promote patient safety, in addition to highlighting how much the care provided by this professional can reduce the risk of unnecessary damage during the care provided in health services.